METODOLOGI KRITIK MATAN HADIS MENURUT AL-ADLABIDARI TEORI KE APLIKASI - Hudaya, Hairul (Fakultas Ushuluddin dan Humaniora IAIN Antasari, 2014)
The validity of hadith is not only seen from the sanad aspect, but also from matan. Hadith scholars set two criteria forthe validity of the matan, both are avoid syaz and âillah. Disability element of matan at syaz lies in the contention ofthe matan. The âillah aspect of matan was because of the additional editorial matan when compared with other. Al-Adlabi formulated the criteria of the validity of matan based on four things namely; 1). It is not contradicting with theKoran; 2). It is not contrary with the valid hadith and sirah nabawiyah; 3). It is not contrary to reason, sense andhistory; and 4). It is similar with the prophetic word. If the formula of al-Adlabiâs matan criticism is seen in aspectsof syaz and âillah, then it appears that his offering is only covers one aspect of the syaz of matan criticism. While thecriteria of âillah have not been accommodated in the rule.